OPTIMALISASI PELAYANAN PUBLIK DALAM MENINGKATKAN AKUNTABILITAS KINERJA ORGANISASI PERANGKAT DAERAH (OPD) KABUPATEN PURBALINGGA - Fitrianingrum, Tyas; Kurniasih, Denok; Tobirin, Tobirin (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
The performance of public service organizations is an important part in realizing state goals. The expected public service standard is to be able to apply the principles of good governance, namely benefit, accuracy, openness, impartiality and public interest. The aim of this research is to find out how to optimize public services in increasing performance accountability in the Regional Apparatus Organization (OPD) of Puralingga Regency in order to realize good governance. The research method used is a qualitative descriptive method, with qualitative data analysis techniques, namely describing and interpreting data obtained in the field through observations and documentation data. The Regional Government through regional apparatus organizations has implemented an accountability system in accordance with existing regulations, however, limited human resources (HR) hinder excellent service to the community. Poor public service performance is partly caused by a lack of accountability in administration. The good performance of regional apparatus organizations is influenced by services that are provided openly and responsibly.